PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN REFILL PERFUME SALSA DI KOTA BATAM - Nurlela, Siti; Mardika, Nanda Harry (LPPM Universitas Putera Batam, 2020)
The quality i of products, prices and promotions provided by the company are in accordance with the desires of consumers in deciding to purchase these products. PT.ATP DZAFIRAH JAYA MAKMUR is one of the perfume refill providers in Batam The best quality products, suitable prices and promotions that continue to be carried out by salsa perfume in accordance with what consumers need can influence purchasing decisions on salsa perfume refill in Batam City. But lately there are still consumers who feel unsure of the product, but there are also some who have begun to understand it. This study aims to determine the effect of product quality, price and promotion on purchasing decisions on salsa perfume refill in Batam City. This study uses multiple linear i regression i analysis. The number of samples was 100 respondents using a random sampling technique Probability sampling Simultaneous.of these results it can be seen that product quality has a positive and significant effect on purchasing decisions of 0.001 <0.05, prices have a significant and positive effect on purchasing decisions of 0.020 ​